Law, technology and cognition : the human element in online copyright infringement - Bosher, Hayleigh (London ; New York : Routledge, Taylor & Francis Group, 2020)
"This book considers a new approach to online copyright infringement. Rather than looking at the subject within a purely technological context, it provides legal analysis from a human perspective. This book highlights that there are three key instances in which the capacity of a human mind intersects with the development of copyright regulation: (1) the development of copyright statutory law, (2) the interpretation of the copyright statutory law the judiciary, and (3) human interaction with new technology. Using a novel framework for constructing digital perspectives, the author, Dr Hayleigh Bosher, analyses the laws relating to online copyright infringement. She provides insights into why the law appears as it does, shedding light on the circumstances of how it came to pass and demonstrates a clear malfunction in the interpretation and application of copyright law to online activities that derives from the disconnect between the technological and the human perspectives. The book proposes putting the human element back into copyright analysis to enable the return of reason where it has been lost, and provide a clearer, more consistent and fair legal regulation of online copyright infringement. Law, Technology and Cognition: The Human Element in Online Copyright Infringement will be of"--
Introduction -- The Human Element in the Story of Online Copyright Infringement -- The Internal and External Perspectives of the Internet -- The Human Element in Reproduction -- Online Copyright Infringement by Storage and Transient Copying -- The Human Element in Communication to the Public -- Communication to the Public : Case Law Analysis -- Concluding the Story
Based on author's thesis (doctoral - Bournemouth University, 2017) issued under the title: A framework using the internal and external perspectives and its application to online copyright infringement : an analysis of copying and communication to the public.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Copyright infringement -- European Union countries; Copyright infringement -- Great Britain; Copyright infringement -- Social aspects; Technological innovations -- Law and legislation; Copyright and electronic data processing